Molecular epidemiology of Japanese encephalitis virus in mosquitoes in Taiwan during 2005-2012. - Chien-Ling Su; Cheng-Fen Yang; Hwa-Jen Teng; Liang-Chen Lu; Cheo Lin; Kun-Hsien Tsai; Yu-Yu Chen; Li-Yu Chen; Shu-Fen Chang; Pei-Yun Shu (Public Library of Science (PLoS), 2014)
Japanese encephalitis (JE) is a mosquito-borne zoonotic disease caused by the Japanese encephalitis virus (JEV). Pigs and water birds are the main amplifying and maintenance hosts of the virus. In this study, we conducted a JEV survey in mosquitoes captured in pig farms and water bird wetland habitats in Taiwan during 2005 to 2012. A total of 102,633 mosquitoes were collected. Culex tritaeniorhynchus was the most common mosquito species found in the pig farms and wetlands. Among the 26 mosquito species collected, 11 tested positive for JEV by RT-PCR, including Cx. tritaeniorhynchus, Cx. annulus, Anopheles sinensis, Armigeres subalbatus, and Cx. fuscocephala. Among those testing positive, Cx. tritaeniorhynchus was the predominant vector species for the transmission of JEV genotypes I and III in Taiwan. The JEV infection rate was significantly higher in the mosquitoes from the pig farms than those from the wetlands. A phylogenetic analysis of the JEV envelope gene sequences isolated from the captured mosquitoes demonstrated that the predominant JEV genotype has shifted from genotype III to genotype I (GI), providing evidence for transmission cycle maintenance and multiple introductions of the GI strains in Taiwan during 2008 to 2012. This study demonstrates the intense JEV transmission activity in Taiwan, highlights the importance of JE vaccination for controlling the epidemic, and provides valuable information for the assessment of the vaccine's efficacy.